Bioprospecting microalgae for biofuel synthesis - Akhtar, Nahid; Wani, Atif Khurshid; Singh, Reena; Chopra, Chirag; Mulla, Sikandar I.; Sher, Farooq; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Elsevier, 2023)
Biofuel has been the center of attention across the world due to its potential as an ecofriendly fuel. Microalgae is known for its biofuel generation owing to its growth rate, economical culture approaches, rich energy content, CO2 fixation capacity, and O2 addition to environment. The cascade of biofuel production involves mass production, harvesting, lipid extraction, and fatty acid conversion by transesterification into biofuel. Despite its applicability, microalgae pose challenges like low lipid yield and slow growth under limiting conditions. Biotechnologic applications can help in the improvement of lipid accumulation, efficient transformation, regulation of associated genes, blocking the competing metabolic pathways, enabling higher biomass, and controlling upstream gene regulators. We present recent developments in the field of biofuel production from microalgae by highlighting the advancement in genetic engineering of different microalgae to maximize the biofuel output. The chapter also elucidates the current status of microalgal-based technologies for biofuel production besides delineating strategies that increase lipid accumulation, growth, biomass production, and carbohydrate content in microalgae through the modification of growth and physiologic conditions.
Keywords: Biodiesel; Biofuel; Genetic engineering; Lipid accumulation; Microalgae; Sustainable energy